Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1080/01635581.2012.712738
|View full text |Cite
|
Sign up to set email alerts
|

The Attenuation of Early Benzo(a)Pyrene-Induced Carcinogenic Insults by Diallyl Disulfide (DADS) in MCF-10A Cells

Abstract: Diallyl disulfide (DADS), a garlic organosulfur compound (OSC), has been researched as a cancer prevention agent; however, the role of DADS in the suppression of cancer initiation in non-neoplastic cells has not been elucidated. To evaluate DADS inhibition of early carcinogenic events, MCF-10A cells were pretreated (PreTx) with DADS followed by the ubiquitous carcinogen benzo(a)pyrene (BaP), or co-treated (CoTx) with DADS and BaP for up to 24 hours. The cells were evaluated for changes in cell viability/prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…G2/M phase cell cycle arrest can reduce proliferation and induce apoptosis by inhibiting the segregation of damaged chromosomes during mitosis (15). DADS has been demonstrated to induce G2/M cell cycle arrest in several cancer cell lines such as colon cancer (11), breast cancer (12) and human gastric cancer cells (13). In the present study, we demonstrated that the percentage of ECA109 cells in DADS treatment groups significantly increased at the G2/M phase in a dosedependent manner (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…G2/M phase cell cycle arrest can reduce proliferation and induce apoptosis by inhibiting the segregation of damaged chromosomes during mitosis (15). DADS has been demonstrated to induce G2/M cell cycle arrest in several cancer cell lines such as colon cancer (11), breast cancer (12) and human gastric cancer cells (13). In the present study, we demonstrated that the percentage of ECA109 cells in DADS treatment groups significantly increased at the G2/M phase in a dosedependent manner (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…DADS has a wide variety of biological activities including antifungal (5), antibacterial (6), antiviral (7), antioxidant (8), antiplatelet and antithrombotic properties (9). Moreover, DADS has gained increasing attention due to its protective effects of cancer development and anticancer effects against different types of malignancies (10)(11)(12)(13). Notably, the apoptotic effects of DADS were even superior to those of chemotherapy agents such as 5-Fu and CTX in human breast cancer cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant attention has been focused on natural radio protective agent in vegetables and fruits. DADS, an oil-soluble compound, extracted from garlic documents as a potent compound to inhibit prostate, lung, gastric and breast cancer progression by inducing apoptosis 12 17 18 29 30 , but the molecular mechanism of protective effect of DADS on carbon ion irradiation remains unclear. In this regard, this study has been undertaken to estimate the protective mechanisms of DADS against carbon ion-induced cell apoptosis at the level of signal transduction pathway in mouse testis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DADS is not only effective at modulating apoptosis proteins but also has potent antiapoptosis capacity 12 . For example, a growing body of evidence indicates that DADS inhibits prostate, lung, gastric and breast cancer progression by inducing apoptosis 12 17 18 . Interestingly, a few studies have reported that pretreatment with DADS attenuated EtOH-induced gastric apoptotic changes, carbon tetrachloride-induced hepatic apoptotic changes, cyclophosphamide-induced urinary bladder epithelial cell apoptosis, and oxidative stress-injured neuronally differentiated PC12 cells, as evidenced by inhibition of cytochrome c release and caspase-3 activation 19 20 21 22 23 .…”
mentioning
confidence: 99%
“…Moreover, initial studies were done using both 100μM and 400μM with approximately the same effect on CCL2 release. Additionally in our previous studies, we demonstrated an optimum overall response using lower doses of DADS in MCF10A human epithelial cells [17]. Therefore, we used 100μM since it would be less likely to have toxic effects on the normal cells at this dose level.…”
Section: Methodsmentioning
confidence: 99%